(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The heat solar energy traditionally is used in greenhouses for ensuring optimal plant vegetation regime in our climatic conditions. Glass verandas built during last centuries at the south side of living houses and summer cottages are appreciated as original use of solar energy. Veranda as light and warm room was used for different household needs and also for social activities. Up-to-date materials and technologies proposes wide spectrum of innovative activities for greenhouses and conservatories. The variable amount of solar energy is possible to smooth out by using accumulation system. In the paper results from vegetable drying experiments are presented. In the research used products – carrots, dry matter of the product at the start 8.5%, chopped product – 9.9%, after desiccation – equilibrium moisture content 10 -11%. The experimental device placed in the room is simulating the processes, which would occur if we use greenhouse for product drying, accordingly making changes in the design of conventional greenhouses by separating drying section from growing section, supplying warm heated in the greenhouse upper layer air from the bottom by forcing it with axial ventilator, and accordingly choosing appropriate accumulation system for energy storage in case when outside air temperature drop occurs.